2019
DOI: 10.1056/nejmoa1901113
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dual Therapies for Lowering Blood Pressure in Black Africans

Abstract: BACKGROUNDThe prevalence of hypertension among black African patients is high, and these patients usually need two or more medications for blood-pressure control. However, the most effective two-drug combination that is currently available for bloodpressure control in these patients has not been established. METHODSIn this randomized, single-blind, three-group trial conducted in six countries in sub-Saharan Africa, we randomly assigned 728 black patients with uncontrolled hypertension (≥140/90 mm Hg while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 33 publications
(24 reference statements)
2
127
3
Order By: Relevance
“…All had some data on blood pressure-lowering efficacy, most reported in terms of office systolic or diastolic blood pressure. Two studies reported only ambulatory blood pressures [37,52], and one study reported only mean arterial blood pressure change [25]. Figure 2 summarises the quality assessment using the Risk of Bias 2 tool.…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…All had some data on blood pressure-lowering efficacy, most reported in terms of office systolic or diastolic blood pressure. Two studies reported only ambulatory blood pressures [37,52], and one study reported only mean arterial blood pressure change [25]. Figure 2 summarises the quality assessment using the Risk of Bias 2 tool.…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
“…There was a sizeably greater 19/9 mmHg drop in SBP/DBP with spironolactone, although the study was small in size. Three studies compared the combination of CCB, diuretics, ACEi or ARBs, and BBs including CREOLE, a recent large parallel RCT of combination therapy in SSA [37]. Our meta-analyses ( Fig.…”
Section: Combination Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, numbers were small. Blood pressure control was optimal overall, with the commonly used mediations mirroring suggestions of their utility in such a cohort (45). A sub-analysis of hypertensives found higher values in cases, suggesting that uncontrolled blood pressure prior to chemotherapy may predispose to cardiomyopathy.…”
Section: Discussionmentioning
confidence: 86%
“…A CCB and thiazide diuretic combination has been previously proven to be effective in blood pressure lowering and stroke prevention in the Felodipine Event Reduction (FEVER) trial . A recent trial in black African population demonstrated that a CCB (amlodipine)/thiazide diuretic (hydrochlorothiazide) combination was superior to an ACEI (perindopril)/thiazide diuretic (hydrochlorothiazide) combination in blood pressure lowering on both clinic and ambulatory measurements . The CCB/β‐blocker combination is recommended in the Chinese guideline mainly because in Chinese secondary and tertiary hospitals, hypertension is managed by cardiologists who believe that β‐blockade is often needed in cardiovascular disease management, especially in association with calcium channel blockade.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%